Ginseng saponins induce store-operated calcium entry in Xenopus oocytes - Jeong, SM; Lee, JH; Kim, S; Rhim, H; Lee, BH; Kim, JH; Oh, JW; Lee, SM; Nah, SY (WILEY, 2004)
1 We investigated the effect of the active ingredients of Panax ginseng, ginsenosides, on store-operated Ca2+ entry (SOCE) using a two-electrode voltage clamp technique in Xenopus oocytes in which SOCE is monitored through Ca2+-activated Cl- currents. 2 Under hyperpolarizing voltage clamp conditions, treatment with ginsenosides produced a biphasic Ca2+-activated Cl- current consisting of a rapid transient inward current and a slowly developing secondary sustained inward current. The transient inward current was inactivated rapidly, whereas the sustained inward current persisted for nearly 10 min. The effect of ginsenosides on the biphasic current was dose-dependent and reversible. The EC50 was 42.8 +/- 11.6 and 46.6 +/- 7.1 mug ml(-1) for the transient and sustained inward current, respectively. 3 In the absence of extracellular Ca2+ ginsenosides induced only a transient inward current but in the presence of extracellular Ca2+ ginsenosides induced the biphasic current. Magnitudes of the sustained currents were dependent on extracellular Ca2+ concentration. Sustained inward current induced by ginsenosides, but not transient inward current, and ginsenoside-induced store-operated Ca2+ (SOC) currents (I-SOC) were blocked by La3+, a Ca2+ channel blocker, suggesting that the sustained inward current and I-SOC was derived from an influx of extracellular Ca2+. 4 Treatment with 2-APB and heparin, which are IP3 receptor antagonists, inhibited the ginsenoside-induced biphasic current. Treatment with the PLC inhibitor, U73122, also inhibited the ginsenoside-induced biphasic current. Intraoocyte injection of ATP-gammaS, but not adenylyl AMP-PCP, induced a persistent activation of ginsenoside-induced sustained current but did not affect the transient current. 5 In rat hippocampal neurons, ginsenosides inhibited both carbachol-stimulated intracellular Ca2+ release and intracellular Ca2+ depletion-activated SOCE. 6 These results indicate that ginsenoside might act as a differential regulator of intracellular Ca2+ levels in neurons and Xenopus oocytes.
Keywords: NICOTINIC ACETYLCHOLINE-RECEPTORS; INTRACELLULAR CA2+ MOBILIZATION; CA2+-ACTIVATED CL-CURRENT; RAT HIPPOCAMPAL-NEURONS; PHOSPHOLIPASE-C; INOSITOL PHOSPHATES; CHLORIDE CURRENT; SENSORY NEURONS; LAEVIS OOCYTES; G-PROTEIN